Network Coding-Based Communications via the Controlled Quantum Teleportation - Dazu Huang; Shaoping Zhu; Dan Song; Ying Guo (Institute of Advanced Engineering and Science, 2013)
Inspired by the structure of the network coding over the butterfly network, a framework of quantum network coding scheme is investigated, which transmits two unknown quantum states crossly over the butterfly quantum system with the multi-photon non-maximally entangled GHZ states. In this scheme, it contains certain number of entanglement-qubit source nodes that teleport unknown quantum states to other nodes on the small-scale network where each intermediate node can pass on its received quantum states to others via superdense coding. In order to transmit the unknown states in a deterministic way, the controlled quantum teleportation is adopted on the intermediate node. It makes legal nodes more convenient than any other previous teleportation schemes to transmit unknown quantum states to unknown participants in applications. It shows that the intrinsic efficiency of transmissions approaches 100% in principle. This scheme is secure based on the securely-shared quantum channels between all nodes and the quantum mechanical impossibility of local unitary transformations between non-maximally entangled GHZ states. Moreover, the generalized scheme is proposed for transmitting two multipartite entangled states. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2031